Fenomena Perempuan sebagai Pemimpin di UIN Maulana Malik Ibrahim Malang: Antara Patriarki dan Feminisme - Nasrulloh Nasrulloh; Khusniyah Utami (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
At the State Islamic University (UIN) Maulana Malik Ibrahim Malang, there are many female faculty and department leaders. Basically, at this time it is not impossible for a woman to become a leader, with the development of feminism in society, women's leadership is not a rare thing. However, the ability of women to occupy the highest positions as leaders who supervise men is still a matter of debate. Patriarchal ideology doubts the position of women as leaders and assumes that not all leadership positions can be occupied by women. This study aims to explain the legal rights of women as leaders with certain limitations. This research is descriptive qualitative, where the researcher will analyze the data gradually after going into the field to make observations through interviews with women who occupy leadership and non-leader positions at UIN Maulana Malik Ibrahim Malang. The results of the interviews were then supported by literature studies from books and scientific research to obtain research results. The method used in this research is qualitative with an inductive approach, because it requires in-depth analysis to find the law of the problems that are carried out in this study. Based on the data obtained, it can be found that the law of women as leaders is permissible and the assumption that women are the weak is not much different from the views of the ignorant society in the past. Therefore, if a woman has good qualities and a capable leadership spirit, then there is no prohibition for her to occupy a leadership position.